2019
DOI: 10.1080/1068316x.2019.1669596
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of truthful and deceptive information

Abstract: Research consistently shows that truthful accounts are richer in detail than deceptive accounts. It is unknown, however, how interviewees strategically regulate the information they provide when their accounts contain both truthful and deceptive information. This study examined how truths and lies interact, and whether interviewees' self-reported strategies reflect such interactions. Participants (n = 144) provided one statement consisting of two elements. We manipulated the veracity of these elements, with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 48 publications
0
22
1
2
Order By: Relevance
“…In line with previous research (e.g., Amado et al, ; Luke, ), we found that entirely truthful statements were richer in detail compared to entirely fabricated statements (Hypothesis 1). In contrast to previous findings by Verigin et al (), we did not find evidence that lies embedded into truthful stories were more richly detailed than lies embedded into completely fabricated stories (Hypothesis 2). Regarding our secondary dependent measures, self‐handicapping strategies emerged as the only (weakly) diagnostic cue to differentiate entirely truthful statements from entirely fabricated statements (Hypothesis 3), and embedded lies from complete lies (Hypothesis 4).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In line with previous research (e.g., Amado et al, ; Luke, ), we found that entirely truthful statements were richer in detail compared to entirely fabricated statements (Hypothesis 1). In contrast to previous findings by Verigin et al (), we did not find evidence that lies embedded into truthful stories were more richly detailed than lies embedded into completely fabricated stories (Hypothesis 2). Regarding our secondary dependent measures, self‐handicapping strategies emerged as the only (weakly) diagnostic cue to differentiate entirely truthful statements from entirely fabricated statements (Hypothesis 3), and embedded lies from complete lies (Hypothesis 4).…”
Section: Discussioncontrasting
confidence: 99%
“…If participants would successfully maintain consistency when embedding their lies into an otherwise truthful statement, their lies could become more richly detailed when surrounded by truthful information. Indeed, recent research compared how interviewees strategically regulate the information they provide when their accounts contain one truthful and one deceptive component and found that lies became more richly detailed when preceded or followed by truthful information compared to when preceded or followed by other lies (Verigin, Meijer, Vrij, & Zauzig, ). The present study aimed to extend these findings by examining the extent to which the embedding of lies into otherwise truthful stories affects the quality of information.…”
Section: Previous Research Findings Regarding Content Cues Of Liars' mentioning
confidence: 99%
“…Not a single veracity assessment tool (or nonverbal lie detection method) employs cut‐off scores and developing those should be the focus of deception researchers examining speech content. Recent research into “verbal baselining” is perhaps a step in the right direction (Palena, Caso, & Vrij, ; Schemmel, Maier, & Volbert, ; Verigin, Meijer, Vrij, & Zauzig, ).…”
Section: Discussionmentioning
confidence: 99%
“…But for this variance to explain the difference in findings between our study and others, one would need to assume that in previous studies, participants in the truth condition were substantially more truthful. This may be unlikely, as other recent research shows it is not rare for liars to include truths [4850], and truthtellers to include lies [5154].…”
Section: Discussionmentioning
confidence: 99%